Raman spectroscopy — Useful tool for studying the catalysts derived from Mo and V-oxyanion-intercalated layered double hydroxides - Dobrea, Iuliana Daniela; Ciocan, Cristina Elena; Dumitriu, Emil; Popa, Marcel Ionel; Petit, Eddy; Hulea, Vasile (Applied clay science, 2015)
Layered double hydroxides with Me-based oxyanions (MeMo, V) in the interlayer gallery were prepared by ion exchange and used as efficient catalysts for the mild oxidation of organic sulfides with H2O2. Raman spectroscopy was used as the main and very efficient technique for the advanced characterization of these materials during their preparation and catalytic use. First, it served for monitoring the progression of the ion exchange during the preparation of the catalysts, and then the Raman spectroscopy provided precise information regarding the type of the oxyanions located in the catalyst structure, before and after the oxidation reaction. [Display omitted] •Raman spectroscopy was used for characterizing LDH containing Mo- and V-oxyanions•These materials are good catalysts for the mild oxidation of thiophenes with H2O2•Mo-LDH were stables catalysts, while the V-LDH suffered major modifications